The Overworld beckons - Keppeler, Jill (Keppeler, Jill. Unofficial Minecraft graphic novel., 2021)
Mike and Maria head back through the Nether portal into the Minecraft world once again. They explore from their new spawn point, plan out a new base, and fend off mobs.